Site Feasibility Analysis in the Design of a Coastal Tourism Area in Lembata Regency - Pius Patty Raya Kapuka; Tigor Wilfritz Soaduon Panjaitan; Mufidah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Lembata Regency possesses coastal potential rich in natural beauty, cultural uniqueness, and marine resources that can be developed into coastal tourism areas. However, this potential has not been fully optimized due to the lack of well-directed site planning based on location feasibility. Therefore, conducting a site feasibility analysis is an essential step to ensure that the development of coastal tourism areas can be carried out effectively, safely, and sustainably. This study aims to formulate relevant site feasibility criteria as the foundation for designing coastal tourism areas in Lembata Regency. The research employs a quantitative approach by conducting field surveys, observations of existing conditions, and comparative studies of several similar coastal areas. The analysis assesses physical site characteristics, environmental quality, accessibility, infrastructure readiness, and natural attraction potential. The findings indicate that site feasibility is strongly influenced by stable soil conditions, well-preserved environmental quality, ease of access to the location, and the availability of supporting facilities surrounding the area. In addition, visual character and natural recreational potential serve as important factors in enhancing tourism appeal. These results are expected to serve as a foundation for designing more strategic and sustainable coastal tourism areas that can improve visitor experience.